Evaluation and improvement of remote sensing-based methods for river flow management. (June 2020) - Samboko, H.T.; Abas, I.; Luxemburg, W.M.J.; Savenije, H.H.G.; Makurira, H.; Banda, K.; Winsemius, H.C.
Abstract: Rapid advancements in technologies open up possibilities for water resource authorities to increase their ability to accurately, safely and efficiently establish river flow observation through remote and non-intrusive observation methods. Low-cost Unmanned Aerial Vehicles (UAVS) in combination with Global Navigation Satellite Systems (GNSS) can be used to collect geometrical information of the riverbed and floodplain. Such information, in combination with hydraulic modelling tools, can be used to establish physically based relationships between river flows and permanent proxy. This study proposes a framework for monitoring volatile, dangerous and difficult to access rivers using only affordable and easy to maintain new technologies. The framework consists of four main components: i) establishment of geometry using airborne photogrammetry and bathymetry; ii) physically based rating curve development through hydraulic modelling of surveyed river sections; iii) determination of non-intrusive observations with for instance simple cameras or satellite observations; and iv) evaluating the institutional and societal impacts of using new technology. To establish this framework, a number of research questions require addressing. First, the factors impacting on accuracy of geometrical information of the floodplain terrain and bathymetry need to be investigated. Second the accuracy of a physically based rating curve compared to a traditional rating curve needs to be established. Third, for rapidly changing river segments, it should be investigated if the collection of occasional snapshots of multiple proxies for flow can be used to assess the uncertainty of river flows. The study finally explores the social and institutional impact of using new technologies for remote river monitoring. If these research gaps are addressed, this may strengthen water manager's ability to observe flows and extend observation networks. Highlights: Site selection criteria for application of UAVs in difficult to access places An evaluation of methods by which geometry is accurately established A combination of the geometry with hydraulic modelling to establish a rating curve An evaluation of discharge accuracy using non-contact observation methods The socio-economical considerations by water authorities for management